Valeurs de la parole féminine : Eloquence et sagesse dans le conte algérien - Larous, Atika dalia (Journal of Human Sciences, 2021)
The tale is a space of expression, mostly frequented by women, they tell it and animate it themselves as characters. The voices of these women are not always audible. In phallocratic societies like Algeria, the female voice is mostly muffled by men. Our research is interested in representations of female speech by its eloquence and wisdom in Algerian tales. Through the chosen tales, we find portraits of voiceless women and in other tales, wise and eloquent female characters who break negative stereotypes which are well established in patriarchal societies. Using a psychological analysis, we will approach the relationship between the "animus" and the intellectual production of these female characters.